2015
DOI: 10.1089/g4h.2014.0106
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure During Xbox Kinect Play in Early Adolescents: The Relationship with Player Mode and Game Enjoyment

Abstract: This study has shown that Kinect play elicits physical activity of moderate intensity. Furthermore, Kinect play is generally enjoyed by both boys and girls. Simultaneous play may be the best suited to increase levels of physical activity in early adolescents who exhibit an inactive lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…HR, V O 2 , and EE were not statistically significantly different from traditional physical activities, and body mass However, exercises performed by children produced greater EE than those performed by adults (p < 0.05), a result that corroborates the findings of Epstein [29]. The effect of sex was not evaluated by Peng, Lin, and Crouse [30]; however, Verhoeven et al [31] did not find significant differences in EE between boys and girls (p > 0.05). Independent of participant characteristics, few studies reported an EE higher than those in the present study (0.12 ± 0.01 kcal•k g − 1 •min − 1 , equivalent to ~31.7 kJ•h − 1 •kg − 1 ).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…HR, V O 2 , and EE were not statistically significantly different from traditional physical activities, and body mass However, exercises performed by children produced greater EE than those performed by adults (p < 0.05), a result that corroborates the findings of Epstein [29]. The effect of sex was not evaluated by Peng, Lin, and Crouse [30]; however, Verhoeven et al [31] did not find significant differences in EE between boys and girls (p > 0.05). Independent of participant characteristics, few studies reported an EE higher than those in the present study (0.12 ± 0.01 kcal•k g − 1 •min − 1 , equivalent to ~31.7 kJ•h − 1 •kg − 1 ).…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies measured the EE elicited by exergame practice [29][30][31] but did not compare these values with the EE reported by the exergames. Therefore, it is difficult to compare our results with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Since the effects of playing modality have been investigated with AVGs practiced as leisure time physical activity played for a short time (i.e., ≤30 minutes; O'Donovan, et al, 2012;Mackintosh, et al, 2016;Monedero, et al, 2017;Verhoeven, et al, 2015), the aim of this study was to evaluate the psycho-physiological (i.e., HR, VO 2 , EE and Rating of Perceived Exertion [RPE]) responses to AVG as a form of a workout played in SP and MP mode, also in relation to gender, by hypothesizing that: 1) MP mode could increase psycho-physiological demands when compared to SP mode, and 2) men could report higher psycho-physiological values than women. ]) college students, with no previous experience in ZFR, volunteered to participate in the study.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has examined the benefits of playing exergames, including greater physical activity levels, 4 enjoyment, 5 self-efficacy, 6 positive mood change, 7 enhancement in physical and cognitive function, 8 improved physical fitness in the elderly, 9 greater energy expenditure, 10 the enhanced intention to engage in other forms of exercise, 11 and physical activity of moderate intensity. 12 Overall, literature has illustrated the health-related impacts of playing exergames. 1,[7][8][9][10][11][12] However, no study has yet investigated whether user characteristics (such as whether the user is optimistic or trying to control his or her weight) moderate the impact of playing exergames on happiness, indicating a research gap.…”
Section: Introductionmentioning
confidence: 99%
“…12 Overall, literature has illustrated the health-related impacts of playing exergames. 1,[7][8][9][10][11][12] However, no study has yet investigated whether user characteristics (such as whether the user is optimistic or trying to control his or her weight) moderate the impact of playing exergames on happiness, indicating a research gap. Research filling this gap can clarify the contingent impact of playing exergames.…”
Section: Introductionmentioning
confidence: 99%